Radiation oncologists' attitudes and beliefs about intensity-modulated radiation therapy and stereotactic body radiation therapy for prostate cancer - Bruce L. Jacobs; Megan Hamm; Flor de Abril Cameron; Jose G. Luiggi-Hernandez; Dwight E. Heron; Jeremy M. Kahn; Amber E. Barnato (BMC, 2020)
Abstract Background To better understand how radiation oncologists perceive intensity-modulated radiation therapy (IMRT) and stereotactic body radiation therapy (SBRT) for prostate cancer and how these perceptions may influence treatment decisions. Methods We conducted semi-structured interviews of radiation oncologists between January-May, 2016. We used a purposeful sampling technique to select participants across a wide range of experience, regions, and practice types. Two trained qualitative researchers used an inductive, iterative approach to code transcripts and identify themes. We then used content analysis and thematic analysis of the coded transcripts to understand radiation oncologists' attitudes and beliefs about IMRT and SBRT. Results Thematic saturation was achieved after 20 interviews. Participants were affiliated with academic (n = 13; 65%), private (n = 5; 25%), and mixed (n = 2; 10%) practices and had a wide range of clinical experience (median 19 years; range 4-49 years). Analysis of interview transcripts revealed four general themes: 1) most radiation oncologists offered surgery, brachytherapy, IMRT, and active surveillance for low-risk patients; 2) there was no consensus on the comparative effectiveness of IMRT and SBRT; 3) key barriers to adopting SBRT included issues related to insurance, reimbursement, and practice inertia; and 4) despite these barriers, most participants envisioned SBRT use increasing over the next 5-10 years. Conclusions In the absence of strong opinions about effectiveness, nonclinical factors influence the choice of radiation treatment. Despite a lack of consensus, most participants agreed SBRT may become a standard of care in the future.